Multicentric data analysis of the learning curve for laparoscopic Shull's repair of pelvic floor defects - Cianci, S.; Ronsini, C.; Riemma, G.; Palmara, V.; Romeo, P.; La Verde, M.; Laganà, A. S.; Capozzi, V.; Andreoli, G.; Palumbo, M.; Torella, M. (Frontiers in Surgery, 2024)
Introduction Pelvic organs prolapse remains a significant health concern affecting millions of women worldwide. The use of native tissues to suspend the apex has acquired relevance in urogynecologic surgery. One of the most commonly used procedures performed without mesh is the technique described by Shull, consisting of suturing the vaginal apex to the uterosacral ligaments. The objective of the study is to evaluate the learning curve of laparoscopic Shull's repair for the correction of pelvic floor defects, including the surgery time and surgical outcomes. Materials and methods This is a retrospective study conducted at the Policlinico G. Martino, University of Messina, Messina, Italy, and Policlinico Vanvitelli, Vanvitelli University, Naples, Italy. All patients affected by grade I-IV POP, consisting of apical prolapse with or without cystocele, and who underwent laparoscopic Shull's technique for prolapse correction were enrolled. The endpoints to estimate the learning curve for the procedure were the percentage of laparoscopic procedures completed, operative time, and the early complication rate. Results A total of 31 laparoscopic Shull repairs were collected for the study. To evaluate the learning curve of the technique, we divided the 31 cases into three different groups: Procedures 0–10; 11–20; 21–31. The parameter for evaluating technique learning was the operative time. Group 21–31 demonstrated an operative time of 97 min (SD 20), compared with 121 min (SD 23) in group 0–10 and 120 min (SD 13) in group 11–20. A comparison of these means through ANOVA showed a p-value of 0.01 for the entire system, and 0.95 for the comparison between 0 and 10 and 11–20, 0.04 for 0–10 vs. 21–31, and 0.02 between 11 and 20 and 21–31. Conclusions The rate of surgical improvement in terms of time became effective after an average of 20 procedures. However, the improvement seems to be effective case by case for surgeons skilled in basic endoscopy.